Implicitly differentiate w.r.t \(x\)
[MATH]\d{y}{x}+\tan(ky)+x\sec^2(ky)\left(k\d{y}{x}\right)=0[/MATH]
Solve for [MATH]\d{y}{x}[/MATH]:
[MATH]\d{y}{x}=-\frac{\tan(ky)}{1+kx\sec^2(ky)}[/MATH]
Apply Pythagorean identity [MATH]\tan^2(\theta)+1=\sec^2(\theta)[/MATH]:
[MATH]\d{y}{x}=-\frac{\tan(ky)}{1+kx(\tan^2(ky)+1)}[/MATH]
From the given equation, we know:
[MATH]\tan(ky)=-\frac{y}{x}[/MATH]
Thus:
[MATH]\d{y}{x}=-\frac{-\dfrac{y}{x}}{1+kx\left(\left(-\dfrac{y}{x}\right)^2+1\right)}=\frac{y}{k(x^2+y^2)+x}[/MATH]
Using the small angle approximation, the original equation becomes:
[MATH]y+kxy=0[/MATH]
[MATH]1+kx=0[/MATH]
[MATH]x=-\frac{1}{k}[/MATH]